Pertanggungjawaban Hukum Pengelola Arisan Online Bermodus Investasi Yang Menimbulkan Akibat Hukum - Ni Putu Yuliana Kemalasari; Irwan Effendi (Jurnal Preferensi Hukum, 2024)
Online lottery is an activity carried out by several people by utilizing the development of technological advances and information by using smartphones in its implementation. Recently, online lottery has been highlighted because it has caused legal consequences, including losses suffered by members, promises of attractive investments and used as a basis for committing criminal acts. The problem that becomes a case in relation to online lottery is the form of responsibility and legal efforts in overcoming it. This research aims to find out the criminal and civil responsibilities of the perpetrators of online lottery who use the argument of investment in deceiving their victims so that the best legal efforts can be found in overcoming this problem. To discuss the related problems, the author formulates them into two problem formulations: first, how is the regulation of online lottery according to positive law in Indonesia and second, how is the legal responsibility of online lottery managers with the investment mode that causes legal consequences. This research uses normative legal research. This normative legal research collects legal materials from primary legal materials, secondary legal materials and tertiary legal materials which are then collected and analysed and then described through a statute approach and case approach. The result of this research is that there is no specific regulation of online lottery according to positive law in Indonesia. However, it can be interpreted that online lottery is an agreement made based on Articles 1330 and 1338 of the Civil Code and is related to the principles and objectives regulated in Articles 3 and 4 of Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions.